x+39+2x=90

Simple and best practice solution for x+39+2x=90 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for x+39+2x=90 equation:



x+39+2x=90
We move all terms to the left:
x+39+2x-(90)=0
We add all the numbers together, and all the variables
3x-51=0
We move all terms containing x to the left, all other terms to the right
3x=51
x=51/3
x=17

See similar equations:

| 7(a-7)-4a=-3(3-a) | | 41y=40y-35 | | 5x+20=13x-20 | | 11x-19+4x-25=8x+19 | | 6(h+1/2)=4h-8 | | 11x-19+4x25=8x+19 | | 3x(x+2)=x-10 | | -31/10=-1+3/2m | | 3e=​4/3 | | -9/j=-45 | | 7x+1x=2 | | 2−2s=​​.75s+13 | | 17-4x=7x | | 2-3-m-5=3m-5m-8-m | | 5r(6r-5)=0 | | 6z-4=3z+5 | | y/14=13 | | 2(1+5n)=82 | | a-14=5 | | -3(m+2)-m=6+3(4-m) | | -3(8v+5)=20 | | 27+2y-10=12y-13-5y | | M+3n=7;n=-2,0,1 | | (6x^2-3x^2)-(2x^2-7x^2)=0 | | 35x-14x-4x-48=40x-8-3x+5 | | 6(9+5x)=54+ | | 8-m-6-m=2(m-3)-2m | | 132-2s=​4/​3​​s+132 | | -20-7g=1-g | | 1.67e-6=2.5(e-10)-7 | | (y+10)=+10 | | 9x-7=5x+41 |

Equations solver categories